Therapeutic setting as an essential component of psychedelic research methodology: Reporting recommendations emerging from clinical trials of 3,4-methylenedioxymethamphetamine for post-traumatic stress disorder - Okano, Lauren; Jones, Gregory; Deyo, Bri; Brandenburg, Alida; Hale, Wesley (Frontiers in Psychiatry, 2022)
Research of psychedelic assisted therapies is at an all-time high, though few studies highlight extra-pharmacological factors that may affect treatment efficacy. One critical set of attributes includes the therapeutic setting itself, which describe the physical and socio-cultural environments in which the drug-assisted session occurs. Despite enduring consensus of the influence of setting, recommendations for establishing and reporting key setting variables remain sparse across clinical trial protocols and published research methodologies. The purpose of this paper is to: 1) present what is known of the influence and implications of setting to psychedelic-assisted therapies, with a particular focus on 3,4-methylenedioxymethamphetamine (MDMA); and 2) propose a set of reporting guidelines for operationalizing and reporting key setting variables in clinical trials of psychedelic-assisted therapies, based on recommendations emerging from clinical trials of MDMA for PTSD. In fact, recommendations should be expanded to “set” - the subject’s mood, expectations, and broader psychological condition - once this is more fully developed in the field. The proposed reporting guidelines offer a means of increasing the volume and variability of data necessary for future empirical examination of key setting attributes influencing treatment efficacy, while preserving practitioner and patient autonomy to co-construct adaptive therapy settings according to their respective needs and expertise. Keywords: Psychedelic therapy, MDMA, Setting, Research Methodologies, Recommendations